Cognitive psychology - Solso, Robert L.; MacLin, Otto H.; MacLin, M. Kimberly (Pearson Education, 2014)
The text features a sequential model of human cognition from sensation to perception, to attention, to memory, to higher-order cognition, and features new cutting-edge coverage of consciousness, cognitive neuroscience, memory and forgetting, and evolutionary psychology.